2013
DOI: 10.1038/bmt.2013.83
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of reduced intensity allogeneic stem cell transplantation and autologous stem cell transplantation when performed as a first transplant strategy in relapsed follicular lymphoma: an analysis from the Lymphoma Working Party of the EBMT

Abstract: Both auto-SCT and reduced intensity allo-SCT (RIST) are employed in the treatment of relapsed follicular lymphoma (FL). We have analysed the outcome of these two transplant procedures when used as a first transplant in this setting. We conducted a retrospective comparison of 726 patients who underwent an auto-SCT and 149 who underwent a RIST as a first transplant procedure for relapsed FL as reported to the Lymphoma Working Party of the European Bone Marrow Transplant. The non-relapse mortality (NRM) was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
54
2
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 37 publications
6
54
2
3
Order By: Relevance
“…With a 3-year OS probability of 29%, survival resembles that reported for second allotransplants for relapsed myeloid malignancies, ranging from 21% after 2 years to 32% after 5 years. [10][11][12][13][14]18 Second allogeneic transplantation for lymphoma relapse K Horstmann et al Importantly, the 3-year NRM of 23% observed here compares well with NRM figures observed in registry studies on first allotransplants in lymphoma, 2,[19][20][21][22][23][24][25] implying that a repeat allotransplant does not seem to be associated with an unacceptable increase in NRM.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…With a 3-year OS probability of 29%, survival resembles that reported for second allotransplants for relapsed myeloid malignancies, ranging from 21% after 2 years to 32% after 5 years. [10][11][12][13][14]18 Second allogeneic transplantation for lymphoma relapse K Horstmann et al Importantly, the 3-year NRM of 23% observed here compares well with NRM figures observed in registry studies on first allotransplants in lymphoma, 2,[19][20][21][22][23][24][25] implying that a repeat allotransplant does not seem to be associated with an unacceptable increase in NRM.…”
Section: Discussionsupporting
confidence: 73%
“…12 Notably, although this subset analysis was limited by small numbers, patients with mantle cell lymphoma and diffuse large B-cell lymphoma did not benefit from a second alloHSCT, whereas long-term PFS after alloHSCT occurred in a substantial proportion of patients with HL, TCL and, in particular, indolent lymphoma. Although the 20-30% PFS plateaus observed seem to be inferior to 3-year PFS rates ranging from 25 to 60% in registry studies on first allotransplants in HL, TCL and follicular lymphoma, 19,20,[25][26][27] this outcome is in line with circumstantial evidence suggesting that these three entities are more susceptible to GVL than aggressive B-cell lymphoma. 24,28 In addition, the finding that in many patients chronic GVHD was absent after alloHSCT_1 but not after alloHSCT_2 is consistent with the conclusion that a second allotransplant might induce an effective allo-response in patients in whom it failed to appear after the first transplant, even if we were not able to show a direct correlation between chronic GVHD and disease control after alloHSCT_2.…”
Section: Discussionsupporting
confidence: 61%
“…16,49 More recent registry studies report a median age between 49 and 57 years. 39,40,44,53 Patients undergoing ASCT continue to be younger patients despite reasonable NRM in the transplanted population. Toxicity in the ASCT population is well managed in the modern era, with NRM ranging from 3% to 5%.…”
Section: Outcomes Of Asct For Inhlmentioning
confidence: 99%
“…Toxicity in the ASCT population is well managed in the modern era, with NRM ranging from 3% to 5%. 44,49,53 A summary of the efficacy outcomes of key ASCT studies is provided in Table 2.…”
Section: Outcomes Of Asct For Inhlmentioning
confidence: 99%
“…In a recently published retrospective analysis of EBMT Registry data on patients in 2 nd or higher treatment line, the survival curves for progression free (PFS) and overall (OS) survival appear to cross in favor of allogeneic SCT beyond the 2 nd or the 8 th year, respectively, despite an adverse risk profile of the allo-transplanted cohorts. 2 So, in the light of these improvements, could allogeneic SCT become the standard treatment for all eligible patients in relapse?…”
mentioning
confidence: 99%